The Influence of Financial Literacy, Financial Behavior, and Locus of Control on the Financial Performance of Micro, Small, and Medium Enterprises (MSMEs) - Permoni, Ni Luh Eka Ayu; Parma, I Putu Gede; Trisnadewi, Ni Kadek Ayu; Tarayani, Ketut Peni (ProBisnis : Jurnal Manajemen, 2025)
This study aims to examine the influence of financial literacy, financial behavior, and locus of control on the financial performance of MSMEs in Kubutambahan Village, Buleleng Regency. The main challenges faced by MSMEs in the area include poor financial management and a lack of confidence in making business decisions, particularly in the aftermath of the COVID-19 pandemic. A quantitative approach was employed, using a survey method with questionnaires distributed to MSME actors. The data were analyzed using multiple linear regression. The results indicate that all three independent variables—financial literacy, financial behavior, and locus of control—have a positive and significant effect on financial performance. Among these variables, financial behavior is the most dominant factor influencing financial performance. These findings highlight the importance of strengthening both financial capacity and psychological resilience of MSME actors as a strategy to improve business competitiveness and sustainability.